Science Fiction in Argentina: Technologies of the Text in a Material Multiverse - Page, Joanna (University of Michigan Press, 2016)
It has become something of a critical commonplace to claim that science fiction does not actually exist in Argentina. This book puts that claim to rest by identifying and analyzing a rich body of work that fits squarely in the genre. Joanna Page explores a range of texts stretching from 1875 to the present day and across a variety of media-literature, cinema, theatre, and comics-and studies the particular inflection many common discourses of science fiction (e.g., abuse of technology by authoritarian regimes, apocalyptic visions of environmental catastrophe) receive in the Argentine context. A central aim is to historicize these texts, showing how they register and rework the contexts of their production, particularly the hallmarks of modernity as a social and cultural force in Argentina. Another aim, held in tension with the first, is to respond to an important critique of historicism that unfolds in these texts. They frequently unpick the chronology of modernity, challenging the linear, universalizing models of development that underpin historicist accounts. They therefore demand a more nuanced set of readings that work to supplement, revise, and enrich the historicist perspective.